3D modeling of austenite based on real microstructure - Prawoto, Yunan; Djuansjah, J.R.P.; Shaffiar, Norhashimah (2012)
This paper discusses about a technique on how to model austenite based on real a microstructure. The steps involved are: Sampling selection, Metallographic preparation, Picture taking, Digitizing the images, Creation of 3D-voxels from multiple 2D images, and 3D meshing technique. As an example, a unit cell of Austenite consisting 9 different constituents are modeled. On the model, conventional continuum mechanics rule can then be applied. The modeling technique enables materials scientists to understand the stress and strain distributions in the microscopic scale that bridge the macroscopic and atomistic understanding in Austenite. The technique can be extended to other microstructure as well.